The prevalence of stalking: Current data from a German victim survey. (November 2015) - Hellmann, Deborah F.; Kliem, Sören
The present study, as part of a large-scale victim survey, examines the prevalence and nature of stalking in a representative German quota sample ( N = 5779). Applying a broad definition of stalking, the lifetime prevalence added up to 15 percent, depending on respondents' age, gender, and immigrant background, as well as household size and relationship status. Conditional inference trees revealed that gender, relationship status, and household size were key factors in identifying victims of stalking. Offenders mostly committed stalking against the opposite gender. This pertains especially to female ( vs. male) victims. In most cases the offender and victim knew each other prior to the stalking. The results are compared with national and international findings. Implications and potential limitations are discussed.